Pengaruh Penambahan Daun Katuk (Sauropus androgynus L. Merr) dan Kunyit (Curcuma domestica) Terhadap Performan dan Rasio Efisiensi Protein Babi Starter - Primurniati, Francois Vemi; Aryanta, I Made S.; Suryani, Ni Nengah (Yayasan Sumber Daya Manusia Cerdas, 2024)
and turmeric (Curcuma domestica) on the performance and protein efficiency ratio of pig starter. The material used was 12 landrace castrated male pigs aged 1-2 months with an initial body weight range of 10,25 kg with a coefficient of variance (CV 19,61%) the design used in this study was a randomized block design (RBD) with 4 treatments and 3 replications. The treatments tried was R0: basal ration (BR), R1: BR + 4% KL, R2: BR + 1% Tu, R3: BR + 4% KL + 1% Tu. Variable measured in this study were ration consumption, body weight gain, ration conversion and efficiency of protein use. The results of the ANOVA analysis showed that treatment had no significant effect (P>0,05) on ration consumption, body weight again, ration conversion and protein efficiency ratio. It was concluded that the addition use katuk leaf 4% (Sauropus andrgynus L.Merr) and turmeric 1% (Curcuma domestica) nor a combined of 4% KL + 1% Tu has the same effect on ration consumption, body weight again, feed conversion, protein efficiency ratio of pigs starter.